Electrochemical Difunctionalization of Alkenes towards the Synthesis of β-Bromoethers under Metal-Free Conditions - Fu, Zhengjiang; Chen, Feiwu; Hao, Guangguo; Yi, Xuezheng; Zeng, Junhua; Cai, Hu (Synthesis, 2023)
A metal-free electrochemical method for vicinal difunctionalization of various alkenes with dibromomethane in alcohol as solvent has been well established to synthesize the corresponding β-bromo-α-alkyloxyalkanes with good functional group tolerance under ambient conditions. Preliminary mechanistic studies indicate the oxidation of bromine source occurs prior to that of alkene substrate with the involvement of bromine radical during electrolysis.
Keywords: difunctionalization; alkene; β-bromoethers; electrochemical transformation; metal-free conditions